Relationship between the solar radiation and surface temperature in Perlis - Ismail, Daut, Prof. Dr.; Mohd Irwan, Yusoff; Safwati, Ibrahim; Muhammmad Irwanto; Gomesh Nair, Shasidharan (Trans Tech Publications, Switzerland., 2013)
Link to publisher's homepage at http://www.ttp.net/1022-6680.html